Active Packaging System from Activated Oil Palm Shells Charcoal Shaped Sachet on Cassava Chips - Jabal Nursito; Rini Hustiany; Alan Dwi Wibowo (Jurnal Teknologi dan Industri Pertanian Indonesia, 2021)
Cassava chips are a type of snack that is fried and prone to rancidity if stored for a while. Cassava chips are added to the material that can adsorb gases, such as oxygen and water vapor, to reduce the occurrence of rancidity using a sachet-shaped adsorbent material. Activated charcoal is one of the gas adsorbents. Activated charcoal used is activated charcoal made from oil palm shells and activated with 20% phosphoric acid. This study aims to analyze the decrease in the quality of cassava chips with an active packaging system during storage for 30 days at 45oC. A total of 30 g cassava chips were packed with a standing pouch in polypropylene type and added activated charcoal from oil palm shells activated by 20% phosphoric acid as much as 1.5 g or 0.75 g which was packed with metalized aluminum plastic or LDPE plastic in the form of sachets. Storage of cassava chips with an active packaging system for 30 days and stored at a temperature of 45oC with a humidity of about 60% and observations are every 3 days in aroma and texture scoring test, moisture content, free fatty acid levels, fat content, and peroxide number. During storage from day 0 to day 30, the cassava chips have decreased the quality of the aroma from typical cassava chips to slightly rancid and the texture from crisp to somewhat not crisp. Moisture content, free fatty acid levels, and peroxide numbers during storage have increased. The fat content has decreasedduring storage. Based on this, cassava chips with the addition of 1.5 g activated charcoal and packaged with metalized aluminum plastic become the best active packaging system.